La vinculación de eventos demográficos : un estudio sobre los patrones de nupcialidad - Juárez, Fátima (El Colegio de México A.C., 1990)
The strategies of nuptiality are interrelated with other important events in the history of the lives of individuals (and families). The times when the most important events of life take place influence one another. The economic and urban development of a society imposes different kinds of restrictions to the individual's decisions regarding the place of residence, the time of marriage, the interval between births and, in general, the lives of people.The object of this paper is to introduce, using the case of Mexico, a new way of linking the interactions between some aspects of the lives of individuals from a dynamic approach; the interaction to urban metropolis is examined. A longitudinal perspective was used for the analysis. The results were derived from the Encuesta Mexicana de Fecundidad (EMF), of 1976-1977, the only source for the country wich includes the history of women on nupciality, fecundity and migration at a national level.The analysis of the patterns of nuptiality shows that marriage in Mexico is almost universal and relatively stable. Consensual unions are close to 16% of the total, this kind of unions is associated with women of low levels of instruction and living in rural areas.The findings of the semi-parametric model for the interaction between nuptiality and migration show that nuptiality influences migration to metropolis; however, the patterns of union remain unchanged by migration to metropolitan areas. In general, the tendency to migrate is higher in unmarried women. Once coupled, women with older cohorts tend to present higher levels of migration if they are legally married than if they live in consensual union. The difference observed is mantained regadless of the social level to wich they belong. However, the covariable "kind of union" looses its importance for the younger cohorts. For the period studied, 1950-1976, women with better socioeconomic conditions have higher migration probabilities, that is to say the most urbanized, legally united to men that have been socialized in a more urban environment and who worked in an agricultural job at the time of marriage.